Situation-Aware QoS Routing Algorithm for Vehicular Ad Hoc Networks - Hashem Eiza, Mahmoud; Owens, Thomas; Ni, Qiang; Shi, Qi (IEEE transactions on vehicular technology, 2015)
A wide range of services has been developed for vehicular ad hoc networks (VANETs), ranging from safety to infotainment applications. An essential requirement for such services is that they are offered with quality of service (QoS) guarantees in terms of service reliability and availability. Searching for feasible routes subject to multiple QoS constraints is, in general, an NP-hard problem. Moreover, routing reliability needs to be paid special attention as communication links frequently break in VANETs. In this paper, we propose employing the situational awareness (SA) concept and an ant colony system (ACS)-based algorithm to develop a situation-aware multiconstrained QoS (SAMQ) routing algorithm for VANETs. SAMQ aims to compute feasible routes between the communicating vehicles subject to multiple QoS constraints and pick the best computed route, if such a route exists. To mitigate the risks inherited from selecting the best computed route that may turn out to fail at any moment, SAMQ utilizes the SA levels and ACS mechanisms to prepare certain countermeasures with the aim of assuring a reliable data transmission. Simulation results demonstrate that SAMQ is capable of achieving a reliable data transmission, as compared with the existing QoS routing algorithms, even when the network topology is highly dynamic.